wrapping zero

Algebra Level 2

IF x^2-x-1=0. THEN FIND x^3-2x+1


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

7 solutions

Niaz Bin Siraj
May 25, 2015

Adyasha Jena
Mar 18, 2015

x^3-2x+1=x(x^2-x-1)+x^2-x+1 {solving the equation we get x^3-2x+1}
=x*0 +x^2-x+1=x^2-x+1 x^2-x+1=1(x^2-x-1)+2
=0+2=2

Alex Delhumeau
May 12, 2015

x 2 x 1 = 0 x^2-x-1=0 , so x 2 x = 1 x^2-x=1 and x 2 = x + 1 x^2=x+1 , and x 3 = x 2 + x x^3=x^2+x .

x 3 2 x + 1 = x 2 x + 1 = x + 1 x + 1 = 2 \Rightarrow x^3-2x+1=x^2-x+1=x+1-x+1=\boxed{2} .

Andrea Palma
Apr 30, 2015

Of course we have

x 0 = 0 x \cdot 0 = -0

Since 0 = x 2 x 1 0 = x^2 - x -1 we have

x ( x 2 x 1 ) = ( x 2 x 1 ) x 3 x 2 x = x 2 + x + 1 x \left( x^2 - x -1\right) = -\left(x^2 - x -1\right) \Longrightarrow x^3 -x^2 -x = -x^2 + x +1

hence

x 3 2 x = 1 x 3 2 x + 1 = 2. x^3 - 2x = 1 \Longrightarrow x^3 - 2x +1 = 2.

Paul Ryan Longhas
Apr 10, 2015

x 2 x 1 = 0 ( x + 1 ) ( x 2 x 1 ) = 0 ( x + 1 ) x^2 - x -1 = 0 \Rightarrow (x+1)(x^2 -x-1) = 0(x+1)

So, x 3 2 x 1 = 0 x 3 2 x = 1 x^3 -2x -1 = 0 \Rightarrow x^3 - 2x = 1

Therefore, x 3 2 x + 1 = ( x 3 2 x ) + 1 = 1 + 1 = 2 x^3 -2x + 1 = (x^3 -2x) + 1 = 1+1 = 2

Aniruddha Bagchi
May 21, 2016

x 2 x 1 = 0 x^2-x-1=0 ›› x 2 = x + 1 x^2=x+1 x 3 = x ( x + 1 ) x^3=x(x+1)

x 3 2 x + 1 x^3-2x+1 = x ( x + 1 ) 2 x + 1 =x(x+1)-2x+1 = x 2 x + 1 =x^2-x+1 ( A s , x 2 x 1 = 0 , s o , x 2 x = 1 ) (As, x^2-x-1=0 , so, x^2-x=1) ›››››› 1 + 1 1+1 = 2 2

Chinmayee Behera
Aug 19, 2015

x^{3}-2x+1=x^{2}-x-1+x(x^{2}-x-1)+2=0+x(0)+2=0+0+2=2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...